Cell-Specific Regulation of Inflammatory Cytokines and Acute-Phase Proteins by the Glucocorticoid Receptor - Rebecca Winkler; Hong Lu (Mediators of Inflammation)
Background. Literature and data mining found abnormal induction of chemokine (C-X-C motif) ligand 1 (CXCL1) and CXCL8 and down-regulation of CXCL2 in inflammatory liver diseases. This study was performed to understand the glucocorticoid receptor’s (GR’s) effects on chemokine and acute-phase protein expression in human liver, in settings of bacterial infection (modeled using LPS) or inflammation (modeled using TNFα). Methods. Primary human hepatocytes (PHH) were treated with combinations of tumor necrosis factor alpha (TNFα), lipopolysaccharide (LPS), and dexamethasone (DEX) for 24 h, following which chemokine mRNA and protein expression were analyzed using qPCR and enzyme-linked immunosorbent assay assays. Dual luciferase assays were performed on transfected cell lines. Mutant CXCL2 promoters were used in dual luciferase assays to identify specific regions of the CXCL2 promoter affected by GR, TNFα, or hepatocyte nuclear factor 4α (HNF4α, a liver-enriched transcription factor). Results. In PHH from donor 1, GR strongly inhibited LPS-induced CXCL1 and CXCL8 translation and transcription, whereas CXCL2 transcription tended to increase with DEX treatment. In PHH from donor 2, DEX treatment inhibited protein expression and secretion of CXCL1 and CXCL8 induced by TNFα and/or LPS, whereas CXCL2 upregulation was largely unaffected by DEX treatment. In nonliver HEK293T cells GR activity inhibited CXCL2 promoter activity. However, in liver-derived HEPG2 cells, GR induced CXCL2 promoter activity. A 407-base pair region upstream of CXCL2 promoter is necessary for full GR functionality in HEPG2 cells. TNFα synergized with HNF4α in inducing CXCL2 promoter activity in HEPG2 cells. Conclusions. GR’s effects on chemokine expression are cell-type specific and chemokine specific. GR down-regulated CXCL1 and CXCL8 in different cell types, whereas the specific activation of CXCL2 in hepatocytes and down-regulation of CXCL2 in nonhepatocytes by GR appears due to cell-specific utilization of CXCL2 promoter. By specifically increasing GR activity in the liver, we may normalize chemokine imbalances and prevent sepsis in inflammatory liver diseases.